Modern Slavery – An Empirical Analysis - Bianca Willert (Universität Rostock, Institut für Volkswirtschaftslehre, 2021)
Contemporarily, modern slavery represents one of the most serious human rights violations. Although most countries officially abolished slavery and ratified the 1926 Slavery Convention of the League of Nations, slavery and slave-like practices still exist in various forms throughout the world. This paper addresses why coercive relationships persist today and investigates how political decision-making, institutional environment and coercive labor practices are interlinked. Moreover, we investigate the interplay between domestic anti-slavery laws and the extent of modern slavery. This paper identifies social and economic determinants of modern slavery using a novel dataset. The panel data contain information on 144 countries and territories from 2002 - 2016 for various types of exploitation of adults and children. We study determinants of modern slavery using cluster analysis and fit a fixed effects model to explain which factors drive exploitation. We find that different types of exploitation are driven by different factors. In addition, we show that slave-sending and slave-receiving countries differ significantly. We study transnational human trafficking and identify which social and economic factors determine this specialization. Moreover, we fit a model using Poisson regression to study why some countries detect victims, originating form more countries, than others do.
Keywords: J47; K42; O15; 330; modern slavery; human trafficking; exploitation; human rights